Heritage in real life: between appreciation and contempt: why are modern Egyptians continuously losing their heritage? - Medhat Wassef (ARCHive-SR, 2025)
Since UNESCO adopted the task of preserving the world's tangible and intangible heritage, the term "cultural heritage" has become known worldwide. However, there seems to be a gap between cultural heritage as a construct made by academic scholars and adopted by UNESCO on one side, and the popular perception of heritage and its significance in daily life on the other side.